1991
DOI: 10.1111/j.1432-1033.1991.tb15844.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain‐acyl‐CoA synthetase activities in peroxisomes and microsomes from rat liver

Abstract: e have investigated the palmitic acid (cl6: o) and cerotic acid (c26: o) activating activities in rat-her microsomes and peroxisomes. The activation of the two fatty acids showed similar dependencies on ATP and coenzyme A, reflected in about equal apparent K, values both in microsomes and peroxisomes. In microsomes and peroxisomes similar apparent K, values for palmitic acid were found (15 pM and 22.8 pM, respectively), whereas apparent K, values for cerotic acid were 8.4 pM and 1 .O pM in microsomes and perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Microsomes, peroxisomes, and mitochondria all contain an identical protein that is designated as a long chain acyl-CoA synthetase (28 -31). Microsomes and peroxisomes, but not mitochondria, also contain a second enzyme, which has not been purified, but it is designated as a very long chain acyl-CoA synthetase (32,33). If 24-carbon acyl-CoAs are hydrolyzed in the cytosol, and not reactivated by mitochondrial long chain acyl-CoA synthetase, it would be an efficient type of control to channel them to peroxisomes for activation and subsequent partial ␤-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Microsomes, peroxisomes, and mitochondria all contain an identical protein that is designated as a long chain acyl-CoA synthetase (28 -31). Microsomes and peroxisomes, but not mitochondria, also contain a second enzyme, which has not been purified, but it is designated as a very long chain acyl-CoA synthetase (32,33). If 24-carbon acyl-CoAs are hydrolyzed in the cytosol, and not reactivated by mitochondrial long chain acyl-CoA synthetase, it would be an efficient type of control to channel them to peroxisomes for activation and subsequent partial ␤-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…If only the pristanoyl-CoA synthesized by the peroxisomal synthetase is available for/3-oxidation within the peroxisome is not known. These fatty acids have to be converted into acyl-CoA esters before being metabolized, and very-long-chain acyl-CoA synthetase (or lignoceroyl-CoA synthetase) activities, dependent on ATP and Mg 2+ [96], have been found to be present in peroxisomes [77,[97][98][99][100], as well as in microsomes, but not in mitochondria (except in [101 ]). Moreover, Bronfman and his collaborators [89,90] have reported that, in rat liver, hypolipidemic drugs such as ciprofibrate undergo activation to CoA-esters and presented results suggesting that the peroxisome proliferators of the fibrate series are activated by the non-specific longchain acyl-CoA synthetase.…”
Section: Activation O F Fatty Acidsmentioning
confidence: 99%
“…Moreover, Bronfman and his collaborators [89,90] have reported that, in rat liver, hypolipidemic drugs such as ciprofibrate undergo activation to CoA-esters and presented results suggesting that the peroxisome proliferators of the fibrate series are activated by the non-specific longchain acyl-CoA synthetase. In recent years, evidence has been brought forward for the existence of a lignoceroyl-CoA synthetase distinct from the palmitoyI-CoA synthetase [74,77,83,97,99,100,[103][104][105][106][107] although this has been questioned by Khishimoto and coworkers [108]. These fatty acids have to be converted into acyl-CoA esters before being metabolized, and very-long-chain acyl-CoA synthetase (or lignoceroyl-CoA synthetase) activities, dependent on ATP and Mg 2+ [96], have been found to be present in peroxisomes [77,[97][98][99][100], as well as in microsomes, but not in mitochondria (except in [101 ]).…”
Section: Activation O F Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) There is a difference in the immunoprecipitability of the two activities . (3) The activities have different sensitivities towards detergents (Singh and Poulos, 1988) and pyrenedodecanoic acid (P10) (Lageweg et al 1991c). (4) There is a lack of competition of C26:o-CoA synthetase by C16:o and vice versa (Wanders et al 1987b).…”
Section: Fatty Acid/~-oxidation In Relation To X-aldmentioning
confidence: 99%